2012
DOI: 10.5301/jn.5000177
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin protects against cisplatin-induced nephrotoxicity by attenuating endoplasmic reticulum stress-induced apoptosis

Abstract: Injection of rHuEPO enhance recovery from CP-induced AKI in rats by ameliorating renal functional impairment and exerting important anti-apoptotic effects. However, rHuEPO inhibited CP-induced AKI by a possible mechanism involving PI3K/Akt activation and the inhibition of ER stress-mediated apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 0 publications
3
28
0
Order By: Relevance
“…ER stress pathway has been implicated to play an important role in CP-induced apoptosis. 34,35 In cells, ER dysfunction can trigger ER stress, resulting in the accumulation and aggregation of unfolded proteins in ER lumen, and prolonged ER stress will initiate the apoptotic pathway. 14,15 Three ER transmembrane receptors including PERK, inositol-requiring enzyme 1 (IRE1), and activating transcription factor 6 (ATF6) regulate the complicated network of physiological responses to ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…ER stress pathway has been implicated to play an important role in CP-induced apoptosis. 34,35 In cells, ER dysfunction can trigger ER stress, resulting in the accumulation and aggregation of unfolded proteins in ER lumen, and prolonged ER stress will initiate the apoptotic pathway. 14,15 Three ER transmembrane receptors including PERK, inositol-requiring enzyme 1 (IRE1), and activating transcription factor 6 (ATF6) regulate the complicated network of physiological responses to ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Injection of recombinant human erythropoietin (rHuEPO) was shown to enhance the recovery from cisplatin-induced acute kidney injury (AKI) in rats by relieving renal functional impairment and exerting significant anti-apoptotic effects. However, rHuEPO inhibited cisplatin-induced AKI through a mechanism possibly involving phosphatidylinositol-3 kinaseÌžAkt activation and inhibition of ER stress-mediated apoptosis (29).…”
Section: Er Stress Is Involved In Cisplatin-induced Cell Death and Ismentioning
confidence: 99%
“…All these abnormalities were reversed by EPO administration (7). Moreover, administration of rhEPO (5000 U/kg) 15 minutes and 2 days before and 2 days after cisplatin administration was effective for inhibiting the cisplatininduced nephrotoxicity by a possible mechanism involving activation of the PI3K/Akt pathway, which is involved in endoplasmic reticulum stress-mediated apoptosis (18). Rjiba-Touati et al demonstrated that pre-administration, co-administration or even post-administration of rhEPO especially in cases of pretreatment with EPO protected the rats against cisplatin-induced renal OS and nephrotoxicity via reduction of malondialdehyde and protein carbonyl levels and prevention of glutathione depletion (19).…”
Section: Epo and Nephrotoxicity Induced By Cisplatinmentioning
confidence: 86%
“…However, it has several side effects such as nephrotoxicity or AKI. Furthermore, the clinical administration of cisplatin is limited due to the increase of dose-dependent nephrotoxicity in about thirty percent of patients (18). In an experimental study by Mohamed et al, 60 rats were divided into three groups including control group (normal saline), cisplatin group (9.0 mg/ kg) and EPO/cisplatin group (100 IU/kg/d).…”
Section: Epo and Nephrotoxicity Induced By Cisplatinmentioning
confidence: 99%